2020
DOI: 10.1088/1361-6463/ab6ea1
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental physicochemical properties of SF6-alternative gases: a review of recent progress

Abstract: Environmental considerations are increasingly taking a front seat in all arenas of our daily lives. Among the major concerns are greenhouse gases and the resulting global warming problem. Although sulfur hexafluoride (SF6) is the most widely used insulation and arc-interruption medium in electrical power equipment, it is an extremely potent greenhouse gas with a very high global warming potential (GWP). Hence, the global power industry has been actively seeking SF6-alternative gases for decades. In recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 146 publications
0
32
0
Order By: Relevance
“…Any C 3 H 2 F 4 -containing insulation equipment must be handled with care to minimize soot formation, which could lead to rapidly deteriorated insulation performance. One potential solution is the use of O 2 [10,12] as part of the mixture to promote recombination into CO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any C 3 H 2 F 4 -containing insulation equipment must be handled with care to minimize soot formation, which could lead to rapidly deteriorated insulation performance. One potential solution is the use of O 2 [10,12] as part of the mixture to promote recombination into CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In [11], the unsaturated double-carbon bonds in C 3 H 2 F 4 drive the fluorinated and hydrogenated molecules to form carbon soot under breakdown or arcing. In [12], it was reported that the addition of O 2 to a fluorinated gas mixture could minimize the formation of solid carbon.…”
Section: Introductionmentioning
confidence: 99%
“…SF 6 /N 2 not only has good insulation performance but also solves the problem of high SF 6 liquefaction temperature. It can effectively reduce the use and emission of SF 6 and relieve the greenhouse effect of SF 6 [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…GIE has become the preferred equipment for establishing smart grids and the important symbol of building a modern substation [1,2]. SF 6 is the main insulation medium of GIE and is a greenhouse gas that cannot be arbitrarily discharged; however, this gas presents an excellent insulation performance, and no alternative gas with better insulating properties and environmental performance is available to date [3,4]. SF 6 is expected to be widely used as the gas insulation medium of high-voltage electrical equipment in the future.…”
Section: Introductionmentioning
confidence: 99%